Awareness and Perception of Artificial Intelligence in Counselling Practice Among Counsellors-in-Training - Soetan, Margaret Kehinde; Akinnusi, Ayorinde Emola (Buletin Konseling Inovatif, 2025)
This study investigated awareness and perception of artificial intelligence in counselling practice among counsellors-in-training. Descriptive survey research design was adopted for this study. The population consisted of all counsellors-in-training (CITs) in Adeyemi Federal University of Education, Ondo. Two hundred (200) counsellors-in-training were randomly selected from Degree three (3) and four (4) as sample for the study. Structured questionnaire was used as instrument to collect data for the study. It was validated by experts in Test and Measurement. Reliability of the instrument was ascertained by using Cronbach’s Alpha statistics mean which yielded a coefficient of 0.83. Data collected was analysed by using frequency counts, percentages and standard deviation. Findings revealed that counsellors-in-training are aware of AI in education and counselling practice which are 87.5% and 61% respectively. The results showed source of awareness among CITs as internet (35%), friends (19%), lecturer (11%) and classmate (4.5%) in succession. The study showed 54% as the level of exposure to AI in counselling practice. Level of perception of usefulness of AI in counselling practice was found as low (43.5%), moderate (52.0%) and high (9%). Level of interest in using AI for counselling practice was revealed as 73% while the limitations of AI for counselling practice are issue of confidentiality (32%), network problem 29%), competence of CITs (23%) and getting consent from the clients (11%). It was therefore concluded that counsellors should work with AI and AI should work with counselling.